Design Criteria for Silicon‐Based Anode Binders in Half and Full Cells. Issue 31 (3rd July 2022) - Deng, Li; Zheng, Yun; Zheng, Xiaomei; Or, Tyler; Ma, Qianyi; Qian, Lanting; Deng, Yaping; Yu, Aiping; Li, Juntao; Chen, Zhongwei
Abstract: While silicon is considered one of the most promising anode materials for the next generation of high‐energy lithium‐ion batteries (LIBs), the industrialization of Si anodes is hampered by the anode's large volume change during the charging and discharging process. In comparison to the traditional graphite anode used in LIBs, the Si anode places more stringent demands on the binder, which must maintain intimate contact between the electrode components and the integrity of the ion and electron transport channels when subjected to frequent large volume changes. The purpose of this review is to cover the recent advances in binder design strategies by examining the molecular structure, chemical functionalities, physical and mechanical properties of the binder materials, as well as the working strategies involved. The challenges in the design of the innovative polymer binder for commercializing Si anodes are discussed, as well as the future development direction and application prospects. Abstract : Design criteria for silicon‐based anode binders in half and full cells: an appropriate binder contributes to the structural stability of the Si electrode; ionic and electrical conductivity, high mechanical characteristics, self‐healing function, and interfacial compatibility are critical considerations in the creation of a suitable binder for Si anodes.